Efficacy of Suture Material in Prophylactic and Rescue Transvaginal Cervical Cerclages: A Retrospective Analysis [35O]. (May 2017) - Daigle, Patrick; Savage, Megan; Bergeron, Michelle; Karlin, Samantha; Hagan, Joseph; Stafford, Irene
Abstract : INTRODUCTION: Cervical cerclage has been used for cervical insufficiency to reduce the risks of premature birth. There is limited data on the efficacy of commonly used cerclage materials. This study was conducted to compare the efficacy of monofilament, braided, and 5mm tape suture in prophylactic and rescue cerclages. METHODS: A chart review of women who received a prophylactic or rescue cerclage between January 2011- December 2015 at Touro Infirmary, New Orleans was performed. The Wilcoxon rank sum test was used to compare gestational age at delivery achieved with different sutures. Fisher's exact test was used to compare gestational age at delivery (≥32, 34, and 37 weeks) between different sutures. SAS version 9.4 was used for data analysis. A 5% significance level was used for hypothesis tests. RESULTS: Thirty four pregnant patients received a cerclage. Sixteen received braided sutures, 12 received monofilament sutures, and 6 received 5 mm tape. The gestational age at delivery was higher for those who received monofilament sutures compared to braided (p= 0.010). The gestational age at delivery for patients who received tape fell between monofilament and braided, but was not significantly different from either (p= 0.367 and 0.782 respectively). A higher proportion of patients who received monofilament sutures delivered at greater than 32 (p= 0.016), 34 (p= 0.024), and 37 (p= 0.017) weeks compared to patients who received braided sutures. CONCLUSION: Our study confirmed that monofilament sutures are superior to braided sutures in achieving greater gestational age at time of delivery, demonstrating that suture material does have an effect on cerclage efficacy.